Early calcitonin levels in medullary thyroid carcinoma: Prognostic role in patients without distant metastases at diagnosis - Sparano, Clotilde; Adornato, Virginia; Puccioni, Matteo; Zago, Elena; Perigli, Giuliano; Badii, Benedetta; Santoro, Roberto; Maggi, Mario; Petrone, Luisa (Frontiers in Oncology, 2023)
Introduction Calcitonin is the most specific marker for medullary thyroid carcinoma, thus, low detectable calcitonin values after surgery can conceal persistent disease. The present study aimed to explore the prognostic role of pre-operative and early calcitonin levels in patients without distant metastases at diagnosis. Methods A retrospective cohort of patients suffering from medullary thyroid carcinoma was considered (N=55). The final disease status, i.e. complete response (undetectable calcitonin levels and negative radiological assessments) or persistent disease (detectable calcitonin levels and/or positive radiological assessments), was deduced from the last available follow-up. Pre-operative and early calcitonin levels (i.e. six months after surgery) have been correlated to several clinical and histological features, according to the final disease status. Results Persistent disease patients showed higher pre-operative and early calcitonin values (p=0.028 and p<0.001, respectively), compared to complete response sub-cohort. Cox-regression models show that early detectable calcitonin increases up to 18-fold the risk of persistent disease, independently from tumour size and pre-operative calcitonin levels (p=0.006). Of note, when considering only patients who finally developed distant metastasis, ROC curve analysis shows that an early calcitonin level ≥16 pg/ml predicts the final disease status with a sensitivity of 89% and a specificity of 82% (AUC=0.911, CI95%: 0.819-1000, p<0.001). Conclusion Calcitonin levels six months after surgery represents an easy and effective predictor of persistent disease for medullary thyroid carcinoma without distant metastasis at diagnosis.